2021
DOI: 10.1063/5.0053187
|View full text |Cite
|
Sign up to set email alerts
|

Beam-driven ECH waves: A parametric study

Abstract: Electron cyclotron harmonic (ECH) waves play a significant role in driving the diffuse aurora, which constitutes more than 75% of the particle energy input into the ionosphere. ECH waves in magnetospheric plasmas have long been thought to be excited predominantly by the loss cone anisotropy (velocity-space gradients) that arises naturally in a planetary dipole field.Recent THEMIS observations, however, indicate that an electron beam can also excite such waves in Earth's magnetotail. The ambient and beam plasma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…ECH waves are known to be excited by the loss cone instability of hot electron velocity distribution (Ashour‐Abdalla & Kennel, 1978; Gao et al., 2020; Horne, 1989; Horne et al., 2003; Liu et al., 2018; Wu et al., 2020). Nevertheless, it is also reported that the generation of ECH waves could be driven by the electron beam distribution (Menietti et al., 2002; Zhang, Angelopoulos, Artemyev, & Zhang, 2021; Zhang, Angelopoulos, Artemyev, Zhang, Liu, 2021). In addition, it is reported by Gao et al.…”
Section: Introductionmentioning
confidence: 99%
“…ECH waves are known to be excited by the loss cone instability of hot electron velocity distribution (Ashour‐Abdalla & Kennel, 1978; Gao et al., 2020; Horne, 1989; Horne et al., 2003; Liu et al., 2018; Wu et al., 2020). Nevertheless, it is also reported that the generation of ECH waves could be driven by the electron beam distribution (Menietti et al., 2002; Zhang, Angelopoulos, Artemyev, & Zhang, 2021; Zhang, Angelopoulos, Artemyev, Zhang, Liu, 2021). In addition, it is reported by Gao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although ECH waves are typically generated by transversely anisotropic electrons [see the first event from Figure 1 and Ashour‐Abdalla and Thorne (1977) and Karpman et al. (1975)], field‐aligned electron streams may also drive ECH generation (see X. Zhang, Angelopoulos, Artemyev, Zhang, & Liu, 2021; X. Zhang, Angelopoulos, Artemyev, & Zhang, 2021, and references therein). Therefore, we may suggest that the difference between events from Figures 1 and 2 are different electron populations responsible for the ECH wave generation: hot, anisotropic electrons trapped into ÎŽB ‖ minima for the first event and cold, field‐aligned electron streams observed at ÎŽB ‖ maxima for the second event.…”
Section: Spacecraft Instruments and Data Setmentioning
confidence: 99%
“…There is no preferential MLT sector for events with correlation or anti‐correlation of whistler‐mode and ECH waves, that is, correlation/anti‐correlation mechanisms shall not be attributed to ULF wave properties or background plasma characteristics, but may depend on properties of electron velocity distributions (relative densities of hot, transversely anisotropic and cold, field‐aligned anisotropic populations, see discussion in X. Fu et al. (2014); X. Zhang, Angelopoulos, Artemyev, and Zhang (2021); Frantsuzov et al. (2022)).…”
Section: Spacecraft Instruments and Data Setmentioning
confidence: 99%
“…The most intense ECH waves occur at L = 5–9, but moderately strong ECH emissions can still be observed up to L = 12 (Zhang et al., 2013), while they generally intensify with increasing geomagnetic activity (Ni, Thorne, Horne, et al., 2011). ECH waves are thought to be excited by the loss cone instability of the ambient plasma sheet electrons (Ashour‐Abdalla & Kennel, 1978), although other generation mechanisms like wave‐wave interactions between chorus waves and ECH waves (Gao et al., 2018) or the excitation by an electron beam distribution (e.g., Zhang, Angelopoulos, Artemyev, & Zhang, 2021; Zhang, Angelopoulos, Artemyev, Zhang, & Liu, 2021) are possible.…”
Section: Introductionmentioning
confidence: 99%